Предмет: Математика,
автор: Sukhrob02
Упростить (a-3b)^2-(a+b)^2
Ответы
Автор ответа:
0
Ответ:2b
Пошаговое объяснение:
(2a-3b)-(a-b)=2а-3b-a+b=a-2b
afr323:
Это же неправильно, там нужно по формуле сокращённо года умножения..
Автор ответа:
0
(a-3b)^2-(a+b)^2=a^2-6ab+9b^2-a^2-2ab-b^2=-8ab+8b^2=-8b(a-b)
Похожие вопросы
Предмет: Математика,
автор: vadimlogatskui
Предмет: История,
автор: ElegyMorton
Предмет: Қазақ тiлi,
автор: tema097777
Предмет: Физика,
автор: narmin7
Предмет: Математика,
автор: 89121445245